Voting "Ford" or Against: Understanding Strategic Voting in the 2014 Toronto Municipal Election1. (9th February 2017) - Caruana, Nicholas J.; McGregor, R. Michael; Moore, Aaron A.; Stephenson, Laura B.
Abstract : Objective: We investigate the phenomenon of municipal‐level strategic voting in a high‐profile mayoral election with a nonpartisan ballot. The rate of strategic voting is calculated, and we investigate whether different types of anti‐candidate attitudes (based on policy or personality) affect strategic behavior. Methods: We use survey data from the 2014 Toronto Election Study. Results: The estimated rate of strategic voting was 1.3 percent. Among those who did cast a strategic ballot, we find that anti‐candidate attitudes did not affect the likelihood of voting strategically—until the source of the dislike is considered, at which point electors who dislike a candidate on the basis of personality are shown to be more likely to cast their ballots strategically. Conclusions: Strategic voting was minimal, and did not affect the election outcome. The type of dislike toward a candidate (either on the basis of policy or personality) affects strategic behavior.